2007
DOI: 10.1007/978-0-387-72124-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Protein Sequences of LcrV Between Epidemic and Atypical Rhamnose-Positive Strains of Yersinia pestis

Abstract: Sequencing of lcrV genes and comparison of the deduced amino acid sequences from ten Y. pestis strains belonging mostly to the group of atypical rhamnose-positive isolates (non-pestis subspecies or pestoides group) showed that the LcrV proteins analyzed could be classified into five sequence types. This classification was based on major amino acid polymorphisms among LcrV proteins in the four "hot points" of the protein sequences. Some additional minor polymorphisms were found throughout these sequence types. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…This classification of the LcrV types accounted for the polymorphism from the consensus sequence and is now different from that assigned by us previously (Anisimov et al , 2007). We found that two of the altaica strains (I-3455 and I-2359) possessed the same type A allele as did the previously sequenced Angola strain, but this subspecies also possessed LcrV of two other types, D (I-2131, I-3519) and E (I-3088, I-3132).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This classification of the LcrV types accounted for the polymorphism from the consensus sequence and is now different from that assigned by us previously (Anisimov et al , 2007). We found that two of the altaica strains (I-3455 and I-2359) possessed the same type A allele as did the previously sequenced Angola strain, but this subspecies also possessed LcrV of two other types, D (I-2131, I-3519) and E (I-3088, I-3132).…”
Section: Discussioncontrasting
confidence: 95%
“… (A part of this work was presented at the 9 th International Symposium on Yersinia , October 10–14, 2006, in Lexington, Kentucky, USA) (Anisimov et al , 2007). …”
mentioning
confidence: 99%
“…Further, F1 capsular antigen is dispensable for virulence (59,60) and the LcrV amino acid sequence has diverged among Y. pestis strains (1, 61). Therefore, the F1-V-based subunit vaccines most likely will not provide optimal protection across all plague-causing strains in humans, specifically those that have been intentionally modified for possible use in terrorist attacks (62,63). The live-attenuated vaccines that promote humoral and cellmediated immune responses may represent a better option for overcoming the above-mentioned shortcomings of the subunit vaccines (9,12).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, enzootic strains are attenuated in many mammalian species, including guinea pigs and primates, but virulent in the rodent Superfamily Muroidea (Anisimov et al, 2004). Although pestoides isolates possess polymorphism in LcrV (Anisimov et al, 2007), a major pCD/pYVencoded regulator, T3SS effector, and virulence factor, it seems unlikely that these differences influence biological activity (Abramov et al, 2007). The purposes of this report are to provide a description of ten typical enzootic isolates and to demonstrate that only three produce functional Zwf while, in stark contrast to epidemic isolates of Y. pestis, all express biologically active AspA.…”
Section: Introductionmentioning
confidence: 99%